(untitled) (Research, Society and Development, 2020)
Transfusion therapy results in the transfusion of specific blood components, which the patient needs to replace, opposing the use of whole blood. This procedure aims to benefit several patients, and to optimize the stocks of blood banks. The presence of anti-erythrocyte antibodies in the serum of patients can cause hemolytic reactions. The identification of these antibodies is extremely necessary for the search for compatible blood components and, consequently, the prevention of transfusion reactions. The objective of this work is to describe the importance of pre-transfusion immunohematological techniques in the blood transfusion process. This is a qualitative bibliographic review based on scientific production based on studies already published. The decision to transfuse a patient must consider the risks and benefits and assess whether there is a real need for blood transfusion. The evaluation occurs through hemoglobin values ​​(for red blood cell transfusions) and platelet values ​​(for blood platelet transfusions) and the clinical aspects of the patient. The introduction of laboratory tests and better donor screening have significantly reduced mortality rates and risks of infections related to this procedure and the most frequent complications today are related to non-infectious causes. Patients who frequently perform blood transfusions may become sensitized, producing alloantibodies, due to the presence of anti-erythrocyte antigens present in the transfused blood bags. These patients have a greater risk of developing transfusion reactions, therefore, the importance of pre-transfusion immunohematological techniques whose main function is to track the presence of irregular antibodies in the recipients and find compatible bags for blood transfusion, decreasing the risk of transfusion reactions and increasing patient safety.